Production of L-asparaginase from natural substrates by escherichia coli atcc 10536 and comparison of physiology parameters - Chia, Vi Vien; Batool, Tahira; Makky, Essam A.; Nina Suhaity, Azmi; Mashitah, Mohd Yusoff (Asian Research Publishing Network (ARPN), 2016)
High demand of L-asparaginase urges the researchers to maximize the production of this enzyme with affordable cost in short period of time. Microbial fermentation is an alternative source for production of L-asparaginase enzyme due to its low cost, easy culturing techniques as well as efficient purification. Addition of substrate is in favour to maximize the production of L-asparaginase where this substrate can be in the form of natural substance or waste products. Excessive amount of waste may cause environmental pollution. Thus, by utilizating waste as substrate is beneficial because the amount of waste can be reduced greaty. This study has shown that both cooked chicken bone and Moringa oleifera seeds as food waste and natural substance respectively can be used to enhance the production of this enzyme which involves fermentation.